Relationship between physical development and physical readiness among skilled wrestlers - Yura Tropin; Vyacheslav Romanenko; Valeriy Goloha; Nataliy Veretelnikova (Kharkiv State Academy of Physical Culture, 2018)
Purpose: to determine the relationship between physical development and physical readiness among qualified wrestlers. Material & Methods: in the study involved thirty qualified wrestlers, aged 19-22 years. For the purpose of analyzing indicators of physical development and physical preparedness, pedagogical testing. Results: the results of the study testify to the homogeneity of the indices of physical development of the athletes under study, the coefficient of variation is in the range from 2,43% to 10,93%. It is revealed that the indices of physical readiness of qualified wrestlers are characterized mainly by small variation in the testing of speed-strength qualities, coordination abilities, general and strength endurance, and average - in the results of special endurance. Conclusion: it is determined that the most informative indicators of physical development are the weight of the wrestler's body, which has a connection with 15 physical preparedness tests, followed by a vital index (12 statistically reliable relationships) and a strength index (11 interrelations).